Beak Line and Eye Alignment as Phenotypic Sexing for Domestic Canaries (Serinus canaria) - Afif Muhammad Akrom; Soedarmanto Indarjulianto; Yanuartono Yanuartono; Trini Susmiati; Alfarisa Nururrozi; Slamet Raharjo; Rief Ghulam Satria Permana; Puveanthan Nagappan Govendan (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Phenotypic sexing of birds is a common practice among the songbird-keeping community, yet it is based on non-reputable information. This study aims to determine the sex of canaries (Serinus canaria) based on the alignment of the eye with the beak line. A total of 26 samples, consisting of six samples of one-month-old canaries (three males and three females based on PCR examination), 20 samples of six-month-old canaries (ten proven breeding pairs) were used in this study. The birds' heads were photographed from the sides, and then the positions of the eyes were compared with the shadow alignment of the beak. The results provided that five young birds and ten adult birds have a beak line alignment under the eye, while ten adult birds and one young bird have a beak line alignment across the eye. The accuracy of sexing using this method was 100% for both female and male adult canaries. However, this result could not be applied to sample that are not yet sexually mature, as two young male birds were found to have beak alignment below the eye. It can be concluded that sexing adult canaries can be performed by observing the eye and beak line's alignment.